ANALISIS PENGARUH PERBEDAAN SUHU DAN WAKTU PENGERINGAN SAMPEL NIKEL ORE TERHADAP HASIL ANALISA LOGAM PADA MATERIAL NIKEL LATERIT MENGGUNAKAN ENERGY DISPERSIVE X-RAY FLUORESCENCE - Fadillah, Rifdah; Gala , Selfina (Journal of Research and Education Chemistry, 2025)
Analysis of the Influence of Differences in Temperature and Drying Time of Nickel Ore Samples on the Metal Analysis Results of Lateritic Nickel Material Using Energy Dispersive X-Ray Fluorescence. This research aims to determine the effect of variations in temperature and drying time on the testing results of metal content in lateritic nickel samples using the Energy Dispersive X-Ray Fluorescence (EDXRF) method, as well as to evaluate the time efficiency in the sample preparation process. The temperature variations used are 105°C, 118°C, and 130°C, each with drying times of 4 hours, 6 hours, and 8 hours. The elements analyzed include Nickel (Ni), Iron (Fe), Silica (SiO₂), and Magnesium Oxide (MgO). The research results indicate that temperature and drying time have a significant impact on the concentration of the elements. A temperature of 105°C tends to produce valid levels, but with high residual humidity. In contrast, a temperature of 130°C increases heavy metal levels, causing volatility of light elements and significant data deviations. The optimal treatment for Ni and Fe values is found at 118°C and 105°C for 6 hours, while SiO₂ and MgO are only optimal at 105°C for 6 hours. However, if the Company's focus is only on Ni and Fe values, then 118°C and 6 hours are recommended as an efficient treatment in terms of working time and do not cause damage to the mineral structure of the sample, as well as optimal conditions in the drying process of laterite nickel sample preparation for analysis using EDXRF. This condition provides a balance between analysis accuracy, data stability, and time efficiency in the laboratory.